COVID-19: Anticipating A Dramatic Collapse And A Recessionary Phase In The World Economy - Ojha, Sandeep; Shubha, Ms. (Archives of Business Research, 2020)
The global nature of the pandemic, along with its great intensity and prolonged duration, will fundamentally alter the business landscape through changing trade flows, asset prices and consumption patterns. The outpouring of whammy ‘Corona Bug’ a public health crunch, an undetectable foe, jolted the attention of the world population towards the strictness that postured the economic vulnerability in almost all the macroeconomic variables such as GDP growth, headline inflation, unemployment rate, investment, current account balance and a measure of political risk which affected nook-n-corner of the world clock in terms of its demand-supply dynamic disruptions. This exploratory study is an attempt to explore the need of the efforts is to put in place a comprehensive action plan and put in the best efforts to implement the plan.